The quality of wine between innovation and tradition. A study of a changing 'Mediterranean drinking culture'. Issue 1 (February 2021) - Beccaria, Franca; Pretto, Albertina
Abstract : Wine consumption is affected by intertwined needs generated by factors such as production and marketing methods, as well as by the individual's desire for social differentiation in a democratised mass drinking culture. Our study sought to determine whether consumption patterns have changed in the Italian province of Trentino and how such changes may have affected the meaning that wine drinkers living in this area assign to the concept of quality in wine. The paper presents a qualitative study (n=57 interviews) carried out in a wine producing region in north-east Italy. In addition to investigating the changes that have taken place in the area's wine drinking culture, the study also focuses on how consumers perceive and define wine quality. The findings show that economic, political and social factors have brought major changes in drinking culture and consumption over the last 50 years. In addition, changes in the wine industry have had a significant impact on how consumers' views on wine quality and its key features have evolved. Nevertheless, the study found that some traditional aspects persist in the drinking culture and still determine the perception of quality.